Penile prosthesis impending erosion: Surgical technique for extracapsular re-implantation reconstruction. Issue 1 (February 2023) - Rebez, Giacomo; Runti, Ottavia; Marco, Lorena Di; Boschian, Riccardo; Rizzo, Michele; Garaffa, Giulio; Liguori, Giovanni; Trombetta, Carlo
Introduction and objectives: Impending erosion is an unusual complication of inflatable penile prosthesis that can strongly impact on patient's morbidity and quality of life. In this case report we present a salvage surgery technique for impending erosion performed in a 57-year-old man. Materials and methods: We present our surgical technique for cylinder reimplantation in an impending erosion of a three-component inflatable prosthesis with a peno-scrotal access and extracapsular reseating of the cylinder. Results: No post-operative complication occurred, and the patient regained full function of the prosthesis after recovery. The surgical site healed well with no signs of infections. Conclusions: Impending erosion is a problematic complication of penile prosthesis; however, can be administered with a salvage technique avoiding the explant of the IPP.